ISOGEOMETRIC ANALYSIS APPLIED TO FREE VIBRATION ANALYSIS OF PLANE STRESS AND PLANE STRAIN STRUCTURES (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Actually Isogeometric Analysis (IGA) have proven high accuracy and efficacy in dynamical problems, openning possibilities to improve the traditional FEM models. The aim of this paper is to test the response of IGA for free vibration problems of plane stress and structures. Based on numerical applications, IGA models have their convergence and accuracy checked and compared with those developed in FEM and GFEM. The results shows high accuracy for IGA models, and reinforce its way as a promising tool.